The impact of health literacy on COVID-19 immunization - Merve Sefa Sayar; Mustafa Özgür Akça; İ̇smail Necati Hakyemez; Ali Asan (Human Vaccines & Immunotherapeutics, 2023)
The COVID-19 pandemic can be controlled by vaccination in addition to public health measures. This study investigate the impact of Health Literacy (HL) on vaccination and COVID-19. 334 patients and patient’s relatives aged 18 to 65 years who were followed up at the Infectious Diseases Clinic between March and July 2022 for reasons other than COVID-19 disease were included in the study. The COVID-19 vaccination status of each participant was queried and the preferred vaccination was recorded on the case form. The mean age was 40.9 years, and 52.4% (n:175) of participants were women. It was found that 82.3% (n:275) of participants had received at least one dose of the vaccine COVID-19. It was found that 17.6% of participants had not been COVID-19 vaccinated. It was found that 60.7% (n:203) of participants received ≥ 2 doses of the mRNA-based viral vaccine. Vaccination rates were found to be significantly lower in patients with ‘inadequate’ HL (p = .047). In addition, the vaccination rate was lower in people aged 39 years and younger and in the presence of one or more chronic diseases. When chronic diseases are present, COVID-19 becomes more severe. On the other hand, the disease shows a moderate clinical picture and plays a significant role in transmission to risk groups in the young population, where vaccination rates are low. This situation in the context of COVID-19 demonstrates once again the importance of informing at-risk groups and the healthy young population about vaccine-preventable diseases.